Pola Komunikasi Pada Organisasi Seribu Senyum Volunteer Surabaya - Qurrata A'yun, Ariza (CV. ITTC INDONESIA, 2025)
Seribu Senyum Volunteer (SSV) as a volunteer organization under the auspices of a humanitarian foundation Seribu Senyum. As an organization engaged in the social and humanitarian field, SSV has a system in the delivery of information when communicating with its members. The purpose of this research is to find out and describe the communication patterns between members of the SSV organization in delivering information and maintaining the communication network system both in terms of obstacles or challenges in it. The research method uses a qualitative approach with data collection techniques through interviews. With various character of its members, ranging from the Daily Management Board (BPH) to its divisions, there are three communication patterns applied to this organization, namely the Y Communication Pattern, carried out by a young philanthropic coordinator who acts as a coach and liaison between the Thousand Smile Foundation and the Thousand Smile Volunteer organization, the head of the health division, and the head of the education division, which emphasizes the hierarchical structure in conveying information and direction. The Star Communication Pattern, applied by the head of the media division which allows each member to interact and exchange information without hierarchy restrictions, and regarding financial transparency is also applied through this communication pattern carried out by the Treasurer, which is to ensure that all members have the same access to financial information. And, the Wheel Communication Pattern, applied by the SSV coordinator to bridge information between the foundation and the community to reduce misunderstandings in the delivery of directions. Keywords: Communication Patterns, Organizational Communication, Humanitarian Organizations